The contribution of phytoplankton in the carbon adsorption and stock during shrimp culture in brackishwater ponds - Bambang Widigdo; MUHAMMAD RIFQI; ALI MASHAR; FITRINA NAZAR; YUSLI WARDIATNO (Society for Indonesian Biodiversity, 2020)
Abstract. Widigdo B, Rifqi M, Mashar A, Nazar F, Wardiatno Y. 2020. The contribution of phytoplankton in the carbon adsorption and stock during shrimp culture in brackishwater ponds. Biodiversitas 21: 5170-5177. In environmental point of view, it is important to determine the potential of adsorption and stock of blue carbon during shrimp farming in ponds with three cultivation technologies namely: extensive/traditional, semi-intensive, and intensive. The aquatic primary productivity approach is used to measure the potential of carbon adsorption in shrimp ponds, while the carbon conversion of chlorophyll-a content is used to measure its stock. The primary productivity and chlorophyll-a content were measured using three ponds for each cultivation technology every ten days from stocking (DOC 0) until the harvest period. The sampling location is in the BLUPPB shrimp pond area of Karawang, West Java - Indonesia. The study concluded that the adsorption and stock of blue carbon varied during shrimp farming in ponds. The primary productivity and chlorophyll-a content of the three cultivation technologies were the significant difference as the results of ANOVA Single Factor. Carbon adsorption average during extensive/traditional, semi-intensive, and intensive shrimp farming in ponds was 1.912832 g C m-3 day-1, 7.097145 g C m-3 day-1 and 8.250195 g C m-3 day-1, respectively. While, the average carbon stock during shrimp farming in extensive/traditional, semi-intensive, and intensive ponds were 0.64896 g m-3, 14.97473 g m-3, and 25.11102 g m-3, respectively.